Dispersion of CeO2 Nanoparticles on Hexagonal Boron Nitride by a Simple CVD Method. Issue 3 (3rd July 2018) - Ge, Mengni; Zhang, Jianfeng; Li, Yahui; Tu, Rong; Goto, Takashi
ABSTRACT: CeO2 nanoparticles were dispersed on hexagonal boron nitride (hBN) supports by a rotary chemical vapor deposition method using Ce(DPM)4 as a precursor at 600°C, and extra oxygen was introduced to assist the decomposition and oxidation of the precursor. A significant composition and structure dependent nature was observed on the oxidation supply rate by eliminating the organic molecules and fragments and assisting the decomposition of the Ce(DPM)4 precursor. The CeO2 nanoparticles were 10-15 nm in diameter, with the measured spacings of the lattice fringes as 0.31 and 0.27 nm, corresponding to (111) and (200) plane, respectively, which are in agreement with the standard data (JCPDS: 34-0394). In addition, with the oxidative decomposition of precursor Ce(DPM)4, CeO2 nanoparticles were produced and then coated on the ceramic surface through the CVD method, presenting the preferred orientation. The deposition mechanism was also discussed. GRAPHICAL ABSTRACT: